Nonmedical Use of Prescription Medications Among Medical Students in Greece: Prevalence of and Motivation for Use. (2nd January 2018) - Papazisis, Georgios; Tsakiridis, Ioannis; Pourzitaki, Chryssa; Apostolidou, Eirini; Spachos, Dimitrios; Kouvelas, Dimitrios
ABSTRACT: Background : Non-medical use of prescription medications has risen to unprecedented levels over the past decade worldwide; however, studies assessing misuse across medical students are sparse. Objectives : The purpose of this study was to1) estimate the lifetime and the past-year prevalence of non-medical use of prescription medications among medical students in Greece 2) identify the motivation for use. Methods : 591 medical students completed an anonymous, self-administered, web-based survey assessing lifetime and past-year prevalence of non-medical use of four classes of prescription drugs (opioid painkillers, tranquillizers, sleeping and stimulant medications). According to the motivation to use the responders were classified into three subtypes (selftreatment, recreational, and mixed). Results : The prevalence of lifetime use was 10.7% for at least one of the four prescription drug classes and 9% of the respondents reported lifetime misuse of multiple categories of prescription drugs. The past-year prevalence was approximately 7.7% for at least one of the four prescription drug classes, while the majority misused the drugs "1-2 times per year". Senior students used tranquilizers more than junior students. Self-treatment and mixed subtypes of tranquillizers misuse was more prevalent among women than men while the self-treatment subtype was the most prevalent subtype in all the four drug classes. Conclusions : This is the first study investigating non-medical use of prescription medications among Greek medical students and indicates a high prevalence of misuse of some categories of prescription drugs, mostly for self-treatment purposes.